Comparative Study of the Immune Response Induced by an Argentinian Classical Strain of IBDV in Two Chicken Breeds - Juan Jaton; María Soledad Lucero; Matías Richetta; Silvina Pinto; María José Gravisaco; Analía Berinstein; Evangelina Gómez; Silvina Chimeno Zoth (Veterinary Medicine International)
The hybrid chicken Negra INTA, which originated at the National Institute of Agricultural Technology (INTA), is the product of the cross between Barred Plymouth Rock females and Rhode Island Red males, and it is used as a laying hen for egg consumption. It has been characterized by productive parameters, but the characterization from an immunological perspective has not been done yet. Infectious bursal disease virus (IBDV) causes a highly contagious viral disease that affects the bursa of Fabricius. Although most chickens are regularly vaccinated against IBDV, this virus still generates negative impacts on production with significant economic losses. The aim of the present work was to compare the immune responses of the Negra INTA hybrid and the White Leghorn layer line to the infection with a field isolate of IBDV. Four-week-old chickens were infected with a single dose of IBDV and at 3, 5, 7, and 30 days postinfection (dpi), bursae were removed, and different parameters were evaluated. Results showed that the reduction of the bursa body (BB) ratio and the histopathological damage were maximum on day 7 postinfection (pi). The viral load was greater in the hybrid Negra INTA at 5 dpi. The humoral immune response between both breeds was similar, although more animals from the commercial line showed higher titers of neutralizing antibodies. Flow cytometry analysis revealed that Bu+ bursal lymphocytes reached a minimum at 7 dpi. Meanwhile, T cell infiltration measured by the percentage of CD3+, CD4+, and CD8+ cells in the bursa was at its maximum at 5 dpi. To our knowledge, this work describes for the first time the pathogenesis and the immune response caused by an Argentinian IBDV isolate in two different chicken lines.